Aveef Interactive Presentation - Bimantara, Afif (AMIKOM ICT AWARD 2010, 2010)
A creation in Digital Media & Animation category that has speciality in creating Dynamic Interactive Presentation for personal or organization. This Dynamic Interactive Presentation can be watched online over the internet. And the content is really dynamic, it can be changed. Updateable text, updateable image and OnLine on internet.